Hydrophilic Interaction Chromatography Analysis of Esculin in Ointments with UV Detection - Abdulla, Fatma H.; Rasheed, Ashraf S. (Current Pharmaceutical Analysis, 2020)
Background: Esculin (ESCN) is used in the pharmaceutical industry with intravenous effect, stimulant and anti-inflammatory capillaries, like vitamin P. It is a significant component of many anti-inflammatory remedies such as esqusan, esflazid and anavenol [14]. It is also found in numerous other remedies available in the market such as proctosone, anustat, and ariproct. Objective: To determine experimental conditions, to elucidate retention behavior of esculin in HILIC mode. Moreover, to suggest new ways to separate and determinate esculin in ointments. Methods: Two hydrophilic columns were obtained by attaching molecules of sulfobetaine to polystyrene- divinylbenzene particles were studied for chromatographic separation of esculin. The various lengths of the chain are used as an investigative instrument for esculin retention conduct. The change of ACN percentage, buffer concentrations and pH of mobile phase in order to study the retention conduct of esculin. Results: A mixed mode hydrophilic interaction and ion exchange is the separation mechanism of esculin. A calibration graph was created for two columns. The concentration range was 8-1200 ng.ml-1, LOD 2.33 and 1.40, RSD% 0.31-1.02, , LOQ 7.07 and 4.25 ng.ml-1, Erel% 0.83 ± 0.68 and 0.545 ± 0.45, Recovery% 100.86 ± 0.68 and 1054 ± 0.45. Conclusion: The findings of the current study introduced new ZIC-HILIC methods for the separation and quantitation of esculin.
Keywords: ZIC-HILIC